Effects of Stakeholder Engagement and Corporate Governance on Integrated Reporting Disclosure - Isnurhadi Isnurhadi; Kurnia Widya Oktarini; Inten Meutia; Mukhtaruddin Mukhtaruddin (Universitas Pasundan, 2020)
Integrated reporting (IR), one of the latest developments in organizational reporting practices, collates important financial and non-financial information in an integrated and concise manner. This study aims to investigate the effects of stakeholder engagement and corporate governance on IR disclosure. In this study, stakeholder engagement was proxied by ownership concentration, the effective tax rate, leverage, and employee compensation, while corporate governance was proxied by the independent board of directors, frequency of audit committee meetings, and gender diversity. Using purposive sampling methods, the sample was selected from a population of companies listed on the LQ45 Index of the Indonesian Stock Exchange. A total of 22 companies that were consistently listed on the LQ45 index during the period 2013–2016 were selected. Panel data regression was employed to analyze the collected data. The results show that only employee compensation had a significant positive effect on IR disclosure while the other variables did not have any significant effect. The results of this study could be used to select the variables that companies must consider when preparing for their IR disclosure to stakeholder.